Bennett, intention and the DDE – The sophisticated bomber as pseudo-problem. (31st August 2017) - Steinhoff, Uwe
Abstract: Arguing against the doctrine of double effect, Bennett claims that the terror bomber only intends to make his victims appear dead. An obvious reply is that he intends to make them appear dead by killing them. I argue that the alleged refutations of this reply rest on a mistaken test question to determine what an agent intends, as Bennett's own test question confirms, and that Bennett is misled by confusing metaphorical death and literal death. Moreover, Bennett's argument is half-hearted anyway, and going the whole way would not only undermine the DDE but also Quinn's revision of it.